Implementasi Kebijakan Penataan Reklame di Kota Tanjungpinang Sesuai Peraturan Walikota Nomor 70 Tahun 2021 Tentang Penyelenggaraan dan Tata Cara Izin Reklame - Darsono, Darsono; Subiyakto, Rudi; Okparizan, Okparizan (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2025)
The implementation of Tanjungpinang Mayor Regulation Number 70 of 2021 concerning the Implementation of Advertisements has created various dynamics since it was implemented in early 2022. This policy aims to improve the aesthetics, safety and usefulness of advertisements in city spatial planning, as well as encouraging Regional Original Income (PAD). However, its implementation faces challenges in the form of protests from billboard entrepreneurs, especially regarding the sealing of billboards that are considered unlicensed. Through a collaborative governance approach, this research explores the importance of coordination between stakeholders, such as the Public Works and Spatial Planning Department, DPMPTSP, BPPRD, and Satpol PP, to resolve conflicts and increase policy effectiveness. This research uses a qualitative method with a descriptive approach. Data was collected through in-depth interviews, documentation and literature study. Data analysis was carried out thematically by focusing on the dynamics of advertising policy implementation in Tanjungpinang based on collaborative governance theory. The results of research (1) show that increasing human resource capacity, (2) improving communication, and (3) increasing awareness among advertising organizers are very important for the successful implementation of this policy. In conclusion, this research emphasizes the need for a collaborative approach between stakeholders to achieve an orderly, safe and aesthetic urban environment in Tanjungpinang.       Keywords: Implementing policies, organizing advertisements, coordinating stakeholders